DOMAIN EXPERTISE IN DATA ANALYTICS: ENHANCING INSIGHTS ACROSS INDUSTRIES - Teena Choudhary, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article investigates the critical role of domain knowledge in enhancing the effectiveness and accuracy of data analysis across various industries. Through a comprehensive examination of case studies in finance, healthcare, and retail sectors, we demonstrate how industry-specific expertise significantly improves data interpretation, metric selection, and the derivation of actionable insights. The article highlights the synergistic relationship between technical analytical skills and deep understanding of industry contexts, revealing that domain experts are better positioned to identify meaningful patterns, develop accurate predictive models, and generate more relevant insights for stakeholders. Furthermore, we provide practical strategies for data analysts to acquire and integrate domain knowledge into their analytical practices, including collaboration with subject matter experts, targeted industry research, and participation in sector-specific training. While acknowledging potential challenges such as cognitive biases and the rapid evolution of industries, this article underscores the importance of domain expertise in the increasingly complex landscape of data analysis. Our findings have significant implications for both aspiring data analysts seeking to specialize in specific industries and organizations aiming to optimize their analytical capabilities